Study of efficiency: standing work vs. ground-work in amateur MMA matches - Lafuente, J.; Merinero, R.; Cardenes, V. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2023)
Introduction. MMA fighters have progressively coalesced into two groups: strikers and grapplers. The subject of the study is to quantify the importance of takedowns and ground work in amateur competitions. Methods. The present study analyzed 279 amateur male MMA matches fought in 2018, using the Tukey Honest Significance Dif- ferences test (Tukey HSD), and quantifying the relationships between different fighting skills and how matches are won. Results and Discussion. The winners of the MMA bouts, on average clearly made more takedowns than the losers, since the most frequent situation was winning the fight and making more takedowns than the opponent (69.9%). After performing the chi-square Pearson test, with a p-value of <0.001, the dependence between the variables - way of winning the fight and performing fewer, the same or more takedowns than the opponent -can be observed. Moreover, when the bouts end by decision, submission or ground KO/TKO, the fighters spend more time fighting on the ground than standing. However, when the match is won by stand up KO/ TKO most of the match takes place standing up. Conclusion. Our results reveal that fighters are most likely to win a match when they employ throws in their standing work, overcoming their opponent. On the other hand, when the victories are via standing KO/TKO, both athletes frequently tie in the number of takedowns; however, when the victory is through submission and KO/TKO via ground and pound, the winner tends to make more takedowns than the loser.